Functional Role of Gonadotrope Plasticity and Network Organization - Edwards, Brian S.; Clay, Colin M.; Ellsworth, Buffy S.; Navratil, Amy M. (Frontiers in Endocrinology, 2017)
Gonadotrope cells of the anterior pituitary are characterized by their ability to mount a cyclical pattern of gonadotropin secretion to regulate gonadal function and fertility. Recent in vitro and in vivo evidence suggests that gonadotropes exhibit dramatic remodeling of the actin cytoskeleton following GnRH exposure. GnRH engagement of actin is critical for gonadotrope function on multiple levels. First, GnRH-induced cell movements lead to spatial repositioning of the in vivo gonadotrope network towards vascular endothelium, presumably to access the bloodstream for effective hormone release. Interestingly, these plasticity changes can be modified depending on the physiological status of the organism. Additionally, GnRH-induced actin assembly appears to be fundamental to gonadotrope signaling at the level of extracellular signal regulated kinase (ERK) activation, which is a well-known regulator of luteinizing hormone (LH) β-subunit synthesis. Lastly, GnRH-induced cell membrane projections are capable of concentrating LHβ-containing vesicles, and disruption of the actin cytoskeleton reduces LH secretion. Taken together, gonadotrope network positioning and LH synthesis and secretion are linked to GnRH engagement of the actin cytoskeleton. In this review, we will cover the dynamics and organization of the in vivo gonadotrope cell network and the mechanisms of GnRH-induced actin-remodeling events important in ERK activation and subsequently hormone secretion.